Enhance the Capacity of Potential Educators to Construct a Comprehensive Understanding of Students with Hearing Impairments by Utilizing Pancasila Principles Through Project-Based Learning - Rohmah Ageng Mursita; Murni Winarsih; Totok Bintoro; Indra Jaya; Shabila Kairunisa; Joleta Silvana Tairas (Journal on Education, 2024)
The objective of this research is to enhance the ability of prospective educators to develop a comprehensive understanding of students with hearing impairments. This study investigates the incorporation of Pancasila principles into a project-based learning framework to meet the educational needs of these students. This study highlights the necessity of providing essential skills and knowledge to prospective teachers to create a conducive classroom environment for students with hearing impairments. This study proposes a unique method to understand and assist students with hearing impairments by integrating Pancasila values into project-based learning. The methodology employed is a mixed methods study to assess the efficacy of this educational approach in enhancing the skills of prospective teachers and the academic achievements of students. The expected outcome is a compilation of principles and tactics that can be utilized by educators to gain a deeper understanding and help children with hearing impairments, thereby fostering collaborative and capacity-building in education.